Anaerobic Co-digestion of Fresh Maize Leaves with Elephant Grass - AD Olugbemide; AO Imasuen; PO Oleghe; JO Efosa (Journal of Applied Sciences and Environmental Management)
Anaerobic co-digestion of maize leaves (ML) with Elephant grass (EG) was studied in a single phase digester at ambient temperature (29+3oC). Special attention was paid to synergistic and antagonistic effect of co-digestion of the substrates on biogas production in order to establish the best blend. Six different treatments were set up based on mixture proportions in digesters labelled A-E. Digester A contained 100% maize leaves (100% ML), which served as control. The compositions of other digesters were as follows: Digester B contained 90% ML and 10% EG, C 80% ML, 20% EG, D 70% ML, 30% EG, and E 60% ML, 40% EG. The initial pH of the digesters varied from 3.94-4.12 while the final pH ranged from 3.01-10.49. 100% ML produced 520ml of biogas at the end of 20 days of the experiment. Digesters B and E had synergistic effects on biogas production with total volume of 870ml and 610ml respectively. However, Digesters C and D had negative effects on biogas yield producing 460ml and 400ml. Percentage decreases of the two digesters were 11.5% and 23.1% respectively. Digester E showed 67.3% higher biogas production compared to digestion of maize leaves alone. @JASEM